Synthesis of fluorescent graphene quantum dots and their application on cellular imaging - Yang, Hao (2017)
Graphene, a form of carbon made of two-dimensional atomic crystal, was first discovered by Geim and Novoselov in 2004. It has fired scholars’ imagination in search of enormous applications because of its high ratio of area to volume, exceptional mechanical pliability, and stable thermal properties. However, in theory graphene has no bandgap, resulting in little photoluminescence (PL), hence significantly limiting their potential in optical imaging and optoelectronic applications. Fortunately, it has been demonstrated that the way to create bandgap in graphene is to change larger graphene into nano-scale graphene quantum dots (GQDs). As their size decreases, quantum confinement effect dominates and thus endows them fluorescence. In this study, GQDs were synthesized respectively by chemical oxidation method and hydrothermal treatment. As-prepared GQDs were characterized by transmission electron microscopy (TEM), atomic force microscopy (AFM), Fourier transform infrared spectroscopy (FTIR), Fluorescence spectroscopy (FS) and ultraviolet-visible absorbance spectroscopy (UV-Vis), GQDs with uniform size and height distribution and superior optical properties were obtained. Besides, the results of photoluminescence spectra demonstrate the prepared GQDs’ superior fluorescence properties and high quantum yield (QY), which increases the possibility of serving as cell imaging agents.The cell viability test by MTT method suggests these prepared GQDs have a good biocompatibility. In the in vitro cell imaging research, cells exhibit the bright green-color when excited by confocal laser scanning microscope (CLSM), which has showed the potential of cellular imaging and probing.